Optimizing the Implementation of Beneficial Ownership in Transfer Pricing in Taxes as a Corporate Crime - Kamilah, Anita; Khan, Md Zubair Kasem (APPTHI, 2021)
Tax is a source of state revenue that plays a major role in financing all state expenditures, including financing national development. The absence of counter-performance that the taxpayer can directly accept is one of the causes of tax crimes committed by corporations through transfer pricing practices, which are difficult to hold accountable, so it is necessary to optimize the application of the principle of Beneficial ownership (BO). The aim of this research is to examine the factors that cause transfer pricing as a form of corporate crime, the application of Beneficial ownership principles in the field of taxation, and the obstacles encountered in implementing Beneficial ownership in the field of taxation along with the solutions. The method is a normative juridical approach, descriptive-analytical research specifications, data types, and sources are derived from secondary data through the support of primary legal materials, secondary legal materials, and tertiary legal materials, and data analysis is carried out qualitatively. The results of the study explain that transfer pricing is a corporate crime that is supported by the use of earnings management, the use of opportunities for special relationships, the support of political connections, and thin capitalization. The application of the principle of Beneficial ownership in the field of taxation means that owners are entitled to enjoy income in the form of dividends, interest and/or royalties, which both individual and corporate taxpayers receive. The obstacles faced in implementing BO in the field of taxation are the weak update of information on Beneficial owners and their changes and partial and sectoral regulations. Abstrak Pajak merupakan salah satu sumber pendapatan negara yang berperan besar dalam membiayai semua pengeluaran negara termasuk membiayai pembangunan nasional. Tidak adanya kontra prestasi yang langsung dapat diterima wajib pajak menjadi salah satu penyebab terjadinya kejahatan di bidang perpajakan yang dilakukan korporasi melalui praktik transfer pricing, yang sulit untuk dimintai pertanggungjawabannya sehingga perlu dioptimalkan penerapan prinsip Beneficial ownership (BO). Tujuan penelitian untuk mengkaji faktor-faktor penyebab terjadinya transfer pricing sebagai bentuk kejahatan korporasi, penerapan prinsip Beneficial ownership di bidang perpajakan dan kendala yang dihadapi dalam menerapkan Beneficial ownership di bidang perpajakan disertai solusinya. Metode pendekatan yuridis normatif, spesifikasi penelitian deskriptif analisis, jenis dan sumber data berasal dari data sekunder melalui dukungan bahan hukum primer, bahan hukum sekunder, dan bahan hukum tersier, dan analisis data dilakukan secara kualitatif. Hasil penelitian menjelaskan bahwa transfer pricing merupakan kejahatan korporasi yang didukung pemanfaatan manajemen laba, pemanfaatan peluang hubungan istimewa, dukungan political connection dan thin capitalization. Penerapan prinsip Beneficial ownership di bidang perpajakan merupakan pemilik yang berhak menikmati penghasilan berupa deviden,bunga dan atau royalti, yang diterima baik wajib pajak perorangan maupun wajib pajak badan. Kendala-kendala yang dihadapi dalam menerapkan (BO) di bidang perpajakan yaitu lemahnya update informasi Beneficial owner maupun perubahannya, serta regulasi yang bersifat parsial dan bersifat sektoral. Kata kunci: Kejahatan Korporasi, Perpajakan, Transfer Pricing, Beneficial Ownership